The VISCACHA survey – I. Overview and first results. Issue 4 (6th February 2019) - Maia, Francisco F S; Dias, Bruno; Santos, João F C; Kerber, Leandro de O; Bica, Eduardo; Piatti, Andrés E; Barbuy, Beatriz; Quint, Bruno; Fraga, Luciano; Sanmartim, David; Angelo, Mateus S; Hernandez-Jimenez, Jose A; et al.
ABSTRACT: The VISCACHA (VIsible Soar photometry of star Clusters in tApii and Coxi HuguA) Survey is an ongoing project based on deep photometric observations of Magellanic Cloud star clusters, collected using the SOuthern Astrophysical Research (SOAR) telescope together with the SOAR Adaptive Module Imager. Since 2015 more than 200 h of telescope time were used to observe about 130 stellar clusters, most of them with low mass (M < 10 4  M⊙) and/or located in the outermost regions of the Large Magellanic Cloud and the Small Magellanic Cloud. With this high-quality data set, we homogeneously determine physical properties from statistical analysis of colour–magnitude diagrams, radial density profiles, luminosity functions, and mass functions. Ages, metallicities, reddening, distances, present-day masses, mass function slopes, and structural parameters for these clusters are derived and used as a proxy to investigate the interplay between the environment in the Magellanic Clouds and the evolution of such systems. In this first paper we present the VISCACHA Survey and its initial results, concerning the SMC clusters AM3, K37, HW20, and NGC 796 and the LMC ones KMHK228, OHSC3, SL576, SL61, and SL897, chosen to compose a representative subset of our cluster sample. The project's long-term goals and legacy to the community are also addressed.